2010
DOI: 10.1038/jid.2009.301
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Fas Gene Expression in Sézary Syndrome Is Associated with Promoter Hypermethylation

Abstract: Sézary Syndrome (SS) is an aggressive leukemic variant of primary cutaneous T-cell lymphoma characterized by the presence of tumor or Sézary cells that generally display a mature memory T-cell immunophenotype. Sézary cells proliferate poorly and therefore their accumulation may be due to defective T-cell homeostasis involving resistance to apoptosis. In this study, we analyzed Fas expression in CD4+ lymphocytes at the mRNA and protein levels in a large cohort of SS patients as compared with healthy controls. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 46 publications
4
34
0
3
Order By: Relevance
“…29 However, we found no evidence of SHP-1 downregulation or promoter methylation in primary SS samples when compared with healthy PBMCs, despite using pyrosequencing, which has sufficient sensitivity to detect hypermethylation against a background of normal cells. 33 It has been previously recognised that the immortalisation of cell lines can itself cause aberrant DNA methylation as a result of selective pressures present during the growth of these cells in culture. 43 Given the lack of changes in DNA methylation or protein expression of SHP-1 in primary cells and the absence of an effect of SHP-1 knockdown in MyLa cells, our results suggest that SHP-1 does not contribute to persistent activation of the JAK-STAT3 pathway in SS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, we found no evidence of SHP-1 downregulation or promoter methylation in primary SS samples when compared with healthy PBMCs, despite using pyrosequencing, which has sufficient sensitivity to detect hypermethylation against a background of normal cells. 33 It has been previously recognised that the immortalisation of cell lines can itself cause aberrant DNA methylation as a result of selective pressures present during the growth of these cells in culture. 43 Given the lack of changes in DNA methylation or protein expression of SHP-1 in primary cells and the absence of an effect of SHP-1 knockdown in MyLa cells, our results suggest that SHP-1 does not contribute to persistent activation of the JAK-STAT3 pathway in SS.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that because of the marked heterogeneity of tumour cell populations, isolation of CD4 þ T-cells is the most appropriate method to enrich for tumour cells without loss of tumour cell sub-populations. 32,33 Lymphoprep (Axis-shield, Kimbolton, UK) gradient centrifugation was used either directly to isolate peripheral blood lymphocytes or following incubation with RosetteSep CD4 þ T-cell enrichment cocktail (Stem Cell Technologies, Grenoble, France) to isolate CD4 þ T-cells.…”
Section: Enrichment Of Ss Tumour Cell Populationsmentioning
confidence: 99%
“…Extrinsic death receptors, including Fas (CD95), play an important role in regulating this process. A number of mechanisms, including promoter methylation [86][87][88], gene mutations [89] and loss of the long arm of chromosome 10 [90] result in diminished Fas expression in CTCL and reduced sensitivity to apoptosis. In addition, promoter methylation and epigenetic instability leading to the inactivation of many tumor suppressor genes, including those involved in the induction of apoptosis, appear to be commonly used mechanisms of lymphomagenesis in CTCL [91].…”
Section: Immunopathogenesismentioning
confidence: 99%
“…4 FAS/TNFRSF6/APO1 that belongs to a set of genes involved in the control of apoptosis is hypermethylated in tumors. [5][6][7] We have previously shown that Fas is overexpressed in low/int-1-risk (LR)-MDS. 8 Conversely, decreased expression of pro-apoptotic Fas, or Fas-associated via death domain (FADD) or increased anti-apoptotic Bcl2 protein in int-2 or HR-MDS could participate in resistance to apoptosis and contribute to disease progression.…”
mentioning
confidence: 99%
“…Variations of the methylation level at FAS promoter have already been described in one CpG island located over the transcription start site ( þ 1) and in a 5 0 -regulatory region located upstream the CpG island in the NIH3T3 cell line transformed by KRAS or in primary tumor cells. [5][6][7]9 Thus, we extensively studied DNA methylation of the promoter region spanning between À 899 and þ 231, which contains 35 CpG dinucleotides, of which 26 belong to a CpG island. The FAS promoter was amplified from bisulfite-treated genomic DNA extracted from CD34 þ cells in 18 LR-MDS, 8 HR-MDS, 11 sAML and 8 controls (Supplementary Table S2 for primers).…”
mentioning
confidence: 99%